PS37 Does the Route to Diagnosis Affect Outcomes for Oesophago-Gastric Cancer Patients. (17th September 2012) - Palser, T; Cromwell, D; Hardwick, R; Riley, S; Greenaway, K; Meulen, J van der
Abstract : Background: The UK Cancer Reform strategy aims to improve early diagnosis but there is little evidence on how the route to diagnosis and affects outcomes for patients with oesophago-gastric (O-G) cancer. We investigated the relationship between the route to diagnosis, patient characteristics, treatment intent and one-year survival among O-G cancer patients Methods: The study was undertaken in 142 English NHS trusts and 30 cancer networks, with data being prospectively collected on patients diagnosed with O-G cancer between October 2007 and June 2009. Route to diagnosis was defined as general practitioner (GP) referral - urgent or non-urgent, hospital consultant referral, or after an emergency admission. The association between patients' route of diagnosis, treatment intent and survival was estimated using logistic regression. Results: Among 14, 102 cancer patients, 66.3% were diagnosed after a general practitioner (GP) referral, 16.4% after an emergency admission, and 17.4% after hospital consultant referral. Of the 9, 351 GP referrals, 68.8% were urgent. Compared to urgent GP referrals, a markedly lower proportion of patients diagnosed after emergency admission had a curative treatment plan (36% v 16%; adjusted odds ratio (OR) = 0.62, 95% CI: 0.52 to 0.74) and a lower proportion of survived one year (43% v 27%; OR=0.78; 0.68 to 0.89). Urgency of GP referral did not affect treatment intent or survival. Routes to diagnosis varied across the 30 cancer networks, with the proportion of patients diagnosed after emergency admission ranging from 8.7% to 32.3%. Conclusion: Outcomes for cancer patients are worse if diagnosed after emergency admission. Networks should examine the causes of large regional variations to reduce rates of diagnosis after emergency admission.